Capturing complex star dune dynamics—repeated highly accurate surveys combining multitemporal 3D topographic measurements and local wind data. Issue 11 (25th July 2022) - Herzog, Manuel; Anders, Katharina; Höfle, Bernhard; Bubenzer, Olaf
Abstract: Morphologies of highly complex star dunes are the result of aeolian dynamics in past and present times. These dynamics reflect climatic conditions and associated forces like sediment availability and vegetation cover, as well as feedbacks with adjacent environments. However, an understanding of aeolian dynamics on star dune morphometries is still lacking sufficient detail, and their influence on formation and evolution remains unclear. We therefore investigate the dynamics of a complex star dune (Erg Chebbi, Morocco) by analysing wind measurements compared to morphometric changes derived from multitemporal high‐accuracy 3D observations during two surveys (October 2018 and February 2020). Using real‐time kinematic global navigation satellite system (RTK‐GNSS) measurements and terrestrial laser scanning (TLS), the reaction of a star dune surface to an observed constant unimodal sand‐moving wind is presented. TLS point clouds are used for morphometric analysis as well as direct surface change analysis, which relates to sand transport. RTK‐GNSS measurements enable the assessment of horizontal crest movement. Observed surface changes lead to the identification of an overall shielding effect, resulting in sand accumulation mainly on windward slopes. Our results point to a self‐sustained dune growth, which has not yet been described in such spatial detail. Steep slopes, often found on star dunes around the globe, seem to partly hinder upslope sand transport. Though a comparatively short observation period, we therefore hypothesize that, besides wind intensity alone, slope angles are more decisive for sand transport than previously assumed. Our methodological approach of combining meteorological data and high‐resolution multitemporal 3D elevation models can be used for monitoring all dune forms and contributes to a general understanding of dune dynamics and evolution. Abstract : The accurate detection of altitudinal surface changes on a star dune compared to climatic data enables the identification of aeolian dynamics and new mechanisms where, besides wind intensity alone, slope angles are more decisive for sand transport than previously assumed. The methodological approach can be transferred to all dune forms, ranging from small barchans to complex and extensive star dunes.